2008
DOI: 10.2174/138620708785739934
|View full text |Cite
|
Sign up to set email alerts
|

Design of Phenotypic Screens for Bioactive Chemicals and Identification of their Targets by Genetic and Proteomic Approaches

Abstract: Cell-based screening using phenotypic assays is a useful means of identifying bioactive chemicals for use as tools to elucidate complex cellular processes. However, the chemicals must display sufficient selectivity and their targets have to be identified. We describe how cell-based screening assays can be designed to maximize the likelihood of discovering selective compounds through the choice of positive readouts, low chemical concentrations and long incubation periods. Examining the potency, efficacy and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In principle, such limitations can be addressed using a cell-based HTS approach. 11 One particularly fruitful method is based upon synthetic growth inhibition. 12 As defined genetically in yeast and bacteria, synthetic growth inhibition occurs when two nonallelic mutations, which individually cause little or no growth defect relative to the corresponding wild-type alleles, synergistically cause lethality or sickness when combined in a double mutant strain.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, such limitations can be addressed using a cell-based HTS approach. 11 One particularly fruitful method is based upon synthetic growth inhibition. 12 As defined genetically in yeast and bacteria, synthetic growth inhibition occurs when two nonallelic mutations, which individually cause little or no growth defect relative to the corresponding wild-type alleles, synergistically cause lethality or sickness when combined in a double mutant strain.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of a positive readout in cell-based screening is an effective way to filter out compounds acting non-specifically. [25][26][27] In independent work, DeMoe et al, Salmela et al and Stolz et al recently reported similar screens for chemical inducers of mitotic slippage using different cell lines and chemical collections. 28,29,47 The screen for inhibitors of mitotic slippage identified several microtubule-targeting agents, which was not surprising given the observation that increasing the concentration of paclitaxel strengthened mitotic arrest.…”
Section: Discussionmentioning
confidence: 89%
“…A positive readout (increased mitotic arrest) was selected over a negative readout (decreased slippage) because positive readout assays are less prone to artefactual results from toxic chemicals. [25][26][27] The paclitaxel concentration was selected to provide ~10% mitotic arrest (20-50 nM), compared to 1-2% for untreated controls (Fig. 4A), to provide a large window to identify chemicals that increase mitotic arrest.…”
Section: Identification Of Chemical Inhibitors Of Mitotic Slippagementioning
confidence: 99%
“…Hit discovery, therefore, is ripe for innovation to produce the screening platforms that can address the large repertoire of undrugged targets. Cell-based screening has emerged as a more physiological alternative to isolated target-based approaches, with the advantage of not presuming which target on a particular pathway will be best to target [40], yet its full adoption has been hindered by robustness issues, difficulties in target deconvolution [41] and the undercurrent of reluctance among medicinal chemists to deal with the potential for complex SARs in the emergent chemical matter. Hit discovery in this sector should have the confidence and freedom to tackle pathway-based assays that provide a repertoire of potential targets and intervention points for chemical matter.…”
Section: Focus For the Futurementioning
confidence: 99%